Development and Evaluation of a Breadfruit Seed Shelling Machine - Orji, C U; Odigboh, E U; Ezeike, GOI (Journal of Agricultural Engineering, 2001)
A mechanized shelling equipment consisting of roller, a fixed concave and a cleaning unit was developed for breadfruit( Treculiar africana).The sheller was evaluated for the moisture content range of 21.70 - 37.50 % (wb) and a clearance range of 0.2cm - 0.5 cm between roller and concave. The results indicated that the highest shelling efficiency of 92% was obtained at the m.c of 37.5% (wb) and clearance setting of 0.5 cm. The actual machine capacity obtained was 101.5kg/hr (86.8% of the theoretical). The cleaning efficiency of the machine was 80%.